Morphological Control for High Performance, Solution-Processed Planar Heterojunction Perovskite Solar Cells - Eperon, G; Burlakov, V; Docampo, P; Goriely, A; Snaith, H (2014)
Organometal trihalide perovskite based solar cells have exhibited the highest efficiencies to-date when incorporated into mesostructured composites. However, thin solid films of a perovskite absorber should be capable of operating at the highest efficiency in a simple planar heterojunction configuration. Here, it is shown that film morphology is a critical issue in planar heterojunction CHNHPbICl solar cells. The morphology is carefully controlled by varying processing conditions, and it is demonstrated that the highest photocurrents are attainable only with the highest perovskite surface coverages. With optimized solution based film formation, power conversion efficiencies of up to 11.4% are achieved, the first report of efficiencies above 10% in fully thin-film solution processed perovskite solar cells with no mesoporous layer. The critical role of perovskite morphology in planar heterojunction perovskite solar cells is probed and understood. Dewetting of perovskite films is minimized, to achieve uniform 100% coverage perovskite layers. Solution cast planar heterojunction solar cells with efficiencies of up to 11.4% are fabricated, a new record for such cells with no mesoporous layer. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.